The putative error prone polymerase REV1 mediates DNA damage and drug resistance in Candida albicans - Michelle R. Agyare-Tabbi; Deeva Uthayakumar; Desiree Francis; Laetitia Maroc; Chris Grant; Peter McQueen; Garret Westmacott; Hajer Shaker; Iwona Skulska; Isabelle Gagnon-Arsenault; Jonathan Boisvert; Christian R. Landry; et al. (npj Antimicrobials and Resistance)
Abstract Antimicrobial-induced DNA damage, and subsequent repair via upregulation of DNA repair factors, including error-prone translesion polymerases, can lead to the increased accumulation of mutations in the microbial genome, and ultimately increased risk of acquired mutations associated with antimicrobial resistance. While this phenotype is well described in bacterial species, it is less thoroughly investigated amongst microbial fungi. Here, we monitor DNA damage induced by antifungal agents in the fungal pathogen Candida albicans, and find that commonly used antifungal drugs are able to induce DNA damage, leading to the upregulation of transcripts encoding predicted error-prone polymerases and related factors. We focus on REV1, encoding a putative error-prone polymerase, and find that while deleting this gene in C. albicans leads to increased sensitivity to DNA damage, it also unexpectedly renders cells more likely to incur mutations and evolve resistance to antifungal agents. We further find that deletion of REV1 leads to a significant depletion in the uncharacterized protein Shm1, which itself plays a role in fungal mutagenesis. Together, this work lends new insight into previously uncharacterized factors with important roles in the DNA damage response, mutagenesis, and the evolution of antifungal drug resistance.